The Immunomodulatory Potential of Cereal Grains - Crowley, Damian; O'Callaghan, Yvonne; O'Brien, Nora M. (Current Nutrition & Food Science, 2018)
Inflammation is a normal response to tissue injury or infection and many chronic diseases are characterised to some extent by the presence of low-grade inflammation. Considerable interest exists in reducing chronic disease risk or managing illnesses through health-promoting dietary ingredients. Cereals are a source of macronutrients, minerals, vitamins and other micronutrients and are also known to contain a range of biologically active substances such as arabinoxylans, β-glucans, cellulose, lignans, lignin, sterols, tocopherols, tocotrienols, alkylresorcinols, phenolic acids and microelements. Cereal grains displaying anti-inflammatory and immunomodulatory activity may have an important role to play in alleviating some of the primary symptoms of inflammation. This paper reviews some of the recent research conducted on cereal grains in relation to their anti-inflammatory and immunomodulatory activity.
Keywords: peptides